Politics, Academic Freedom, and Social Justice - Ginny Boehme (Issues in Science and Technology Librarianship, 2024)
The main letter from the editors of this special issue ends with a very optimistic message about the potential "long future of social justice research...in the online pages of ISTL." However, recent events have prompted us to temper this with an open acknowledgement of the difficult political context of this research.